Penerapan E-Government dalam Tata Kelola Kearsipan pada Badan Pengawas Pemilihan Umum Provinsi Gorontalo - Syahran Lamusu; Ismet Sulila; Sri Yulianti Mozin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study explores the implementation of e-Government within the context of Bawaslu (Election Supervisory Agency) and its impact on governance and public trust. The results reveal that, from the support aspect, the success of e-Government implementation is largely driven by the commitment of leadership, which provides essential policies, human resources (HR) training, and technological facilities. However, challenges remain in terms of limited infrastructure and budget constraints at the district and city levels. Regarding the capacity aspect, Bawaslu already possesses competent HR, particularly among the younger generation, and adequate infrastructure. Nevertheless, there is still a need for improvement in the distribution of employee capabilities through continuous training and mentoring. Lastly, from the value perspective, e-Government has proven to deliver tangible benefits, such as increased efficiency, transparency, accountability, and an enhanced public trust in the institution. However, further efforts are required in areas such as system socialization, maintenance, and data security to maximize these benefits. This research highlights the importance of continuous development in both human and technological resources to ensure the optimal success of e-Government initiatives in enhancing governance and service delivery.